The prostate cancer bone marrow niche: more than just ‘fertile soil' - Pedersen, Elisabeth A (Nature Publishing Group, 2012)
The hematopoietic stem cell (HSC) niche in the bone marrow has been studied extensively over the past few decades, yet the bone marrow microenvironment that supports the growth of metastatic prostate cancer (PCa) has only been recently considered to be a specialized ‘niche' as well. New evidence supports the fact that disseminated tumor cells (DTCs) of PCa actually target the HSC niche, displace the occupant HSCs and take up residence in the pre-existing niche space. This review describes some of the evidence and mechanisms by which DTCs act as molecular parasites of the HSC niche. Furthermore, the interactions between DTCs, HSCs and the niche may provide new targets for niche-directed therapy, as well as insight into the perplexing clinical manifestations of metastatic PCa disease.